Med delom in celoto - Fikfak, Jurij (Traditiones (Ljubljana), 2008)
Researchers dealing with folk culture, lifestyles, cultural objectifications, empirical study of culture, and so on continually deal with the question of how to represent the "whole" - that is, the totality of life of particular community in a given environment: which statements, informants, and so on to select and present. This article examines certain realizations characteristic of twentieth-century studies in ethnography, ethnology, and cultural anthropology.
Keywords: ethnology; etnologija; slovenska ljudska kultura; metodologija; scientific method; znanstveno raziskovanje